Corporate Governance in South African State-Owned Enterprises - Kikeri, Sunita (World Bank, Washington, DC, 2018)
Drawing from the presidential review commission review, and from other available materials, this background note for the South Africa systematic country diagnostic synthesizes the key issues and recommendations for improving state-owned enterprise (SOE) performance, focusing on the largest national level commercial SOEs in infrastructure and other key sectors. Based on available materials, the note provides an overview of key governance constraints affecting SOE performance and suggests areas for improvement.